Pertumbuhan dan Produktivitas Tanaman Bawang Merah (Allium ascalonicum L. var.Tiron) Dengan Perlakuan Gracilaria verrucosa Sebagai Penjerap Air Pada Tanah Pasir - Umami, Arif -; Darmanti, Sri -; Haryanti, Sri - (Bioma : Berkala Ilmiah Biologi, 2011)
The aims of this study to determine effect of treatment G.verrucosa as water trappers on growth andproductivity of onions crops grown on sandy soil. The research using CRD with factorial pattern ( 3 x 4 ). The firstfactor is the size of pieces G.verrucosa (U1 =flour, U2 =0.25 cm, U3 = 0.5 cm). The second factor is thecomposition of the mixture G.verrucosa: sand (T1 = 0%: 100%, T2 =10%: 90%, T3 =20%: 80% and T4 =30%:70%). The data obtained were analyzed by ANAVA at the level of significance of 95% followed by Duncan's at95% significance level. The results showed that the addition of G. verrucosa able to increase growth and cropproductivity compared with the onion crops grown on sandy soil only. The most influential medium for plantgrowth is a mixture of onion G. verrucosa with sand on the composition of 20%: 80% with G. verrucosa in all sizes,while the most influential medium for the production of onion crop is a mixture of G. verrucosa in all sizes with asandy soil with a ratio of 10%: 90%.